Association study Between Glycemic Control and Recurrence Rate of Urinary Tract Infections in diabetic patients Type 2 in Tishreen hospital - فضلية يسرا; أريج بوبو; حسين سعيد (Latakia University Journal -Medical Sciences Series, 2022)
Introduction: Diabetic is considered the sickness of the century, and it has many complications, such as increased susceptibility to infections generally, and urinary tract infections specially.So we discussed in our study a subject about: Association study Between Glycemic Control and Recurrence Rate of Urinary Tract Infections in diabetic patients, and its tangible effect on preventing recurrence of urinary tract infections. Methods: our study include 92 patients with diabetic type 2 and affected with urinary tract infection broved with bacterial culture, The patient were founded either in the department of the endocrinology or they were OUT PATIENT REVIEWERS. Results: The hemoglobin values ranged from 6,5 % to 12,9 % with middle value (8,82+-1,43%). The duration of diabetic ranged from 3 months to 30 years with middle value (13,3_7,9) year The diabetic patient treatment were oral depressors used at 58 patient 53%, And Insulin used at 34 patient 47%. About infection place: it was upper in 49 patients (53,3%), and lower in 43 patients (47,7%) . We found that both (advanced age p<0,001, increased of the duration of the diabetes p=0,002, urinary tract infection hospitalization p<0,001, and insulin treatment p=0,003) Come with increased upper tract infection rate compared to lower tract infection We found that increased urinary tract infection rate during last year combined with bad glycemic control p<0.001, female sex p=0.003 -Advanced age p<0.001, duration of diabetes p=0.002. We found that the most sensitive antibiotic with e-coli infection is Nitrofurantoin in the first degree then Amikacin in the second degree About another negative germs the most sensitive antibiotic is amikacin, then tegecicline. But about positive cocci we found that the most sensitive antibiotics are vancomycin and linzolide Conclusion: WE CONCLUDE THAT GOOD GLYCEMIC CONTROL REDUCES THE URINARE TRACT INFECTION.THE DURATION OF DIABETIS, INCREASE THE RECCURENCE OF URINARY TRACT INFECTION.THE INDISCRIMINATE USE OF THE ANTIBIOTIC, CONSIDERED ACCUSED FACTOR WTH RECCURENCE OF THE URINARY TRACT INFECTION.